Distribution and protective function of pituitary adenylate cyclase-activating polypeptide in the retina - Nakamachi, Tomoya; Matkovits, Attila; Seki, Tamotsu; Shioda, Seiji (Frontiers in Endocrinology, 2012)
Pituitary adenylate cyclase-activating polypeptide (PACAP), which is found in 27- or 38-amino acid forms, belongs to the VIP/glucagon/secretin family. PACAP and its three receptor subtypes are expressed in neural tissues, with PACAP known to exert a protective effect against several types of neural damage. The retina is considered to be part of the central nervous system, and retinopathy is a common cause of profound and intractable loss of vision. This review will examine the expression and morphological distribution of PACAP and its receptors in the retina, and will summarize the current state of knowledge regarding the protective effect of PACAP against different kinds of retinal damage, such as that identified in association with diabetes, ultraviolet light, hypoxia, optic nerve transection, and toxins. This article will also address PACAP-mediated protective pathways involving retinal glial cells.